Pengembangan Model Pembelajaran Ekstrakurikuler Tahfizh Untuk Meningkatkan Hafalan Al-Qur’an Siswa di SMP IT Al Aziz Sibuhuan Padang Lawas - Makmur Hasan Nasution; Anhar Anhar; Hamdan Hasibuan (Sekolah Tinggi Ilmu Tarbiyah Padang Lawas Gunung Tua, 2025)
Some students have not yet achieved the Qur’an memorization targets in the tahfizh extracurricular program. This is due to the unstructured nature of the activities, the lack of variety in teaching methods, and the absence of a learning model suited to the characteristics of junior high school students. This condition hinders the school's expected memorization goals, thus necessitating R&D research to develop a tahfizh learning model. This study adopts the Borg and Gall research and development approach, covering preliminary study to final model refinement. The research subjects included tahfizh instructors and students. The results showed that content validation scored 82% (highly valid), language validation 80% (valid), and media validation 80% (valid). These three aspects met the feasibility criteria for testing and implementation. The practicality test showed a score of 74.8% (practical). Therefore, the tahfizh learning model is not only theoretically valid but also practical and effective when applied at SMP IT Al Aziz Sibuhuan.